2021
DOI: 10.21203/rs.3.rs-808746/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-nucleus lung transcriptomics and inflammatory responses in lethal COVID-19 reveal potential drugs in advanced-stage clinical trials

Abstract: There is pressing urgency to identify drugs that allow treating COVID-19 patients effectively. Respiratory failure is the leading cause of death in patients with severe COVID-19, and the host inflammatory response at the lungs remains poorly understood. Therefore, we retrieved data from postmortem lungs from COVID-19 patients and performed in-depth in silico analyses of single-nucleus RNA sequencing data, inflammatory protein interactome network, functional enrichment, and shortest pathways to cancer hallmark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Furthermore, baricitinib prevents viral endocytosis by inhibiting kinase signaling and inhibits cytokine release by blocking JAK1/2 signals. Baricitinib was rapidly transferred from intra-silicon studies to clinical trials ( 161 ). The study showed that healthy individuals treated with baricitinib had varying degrees of inhibition of cytokine-dependent phosphorylated STAT (pSTAT).…”
Section: Jak Inhibitors As Therapeutic Agents Against Covid-19mentioning
confidence: 99%
“…Furthermore, baricitinib prevents viral endocytosis by inhibiting kinase signaling and inhibits cytokine release by blocking JAK1/2 signals. Baricitinib was rapidly transferred from intra-silicon studies to clinical trials ( 161 ). The study showed that healthy individuals treated with baricitinib had varying degrees of inhibition of cytokine-dependent phosphorylated STAT (pSTAT).…”
Section: Jak Inhibitors As Therapeutic Agents Against Covid-19mentioning
confidence: 99%